"I Am Okay With It, But I Am Not Going to Do It": The Exogenous Factors Influencing Non-Participation in Medical Assistance in Dying. (October 2021) - Brown, Janine; Goodridge, Donna; Thorpe, Lilian; Crizzle, Alexander
Medical assistance in dying (MAID) processes are complex, shaped by legislated directives, and influenced by the discourse regarding its emergence as an end-of-life care option. Physicians and nurse practitioners (NPs) are essential in determining the patient's eligibility and conducting MAID provisions. This research explored the exogenous factors influencing physicians' and NPs' non-participation in formal MAID processes. Using an interpretive description methodology, we interviewed 17 physicians and 18 NPs in Saskatchewan, Canada, who identified as non-participators in MAID. The non-participation factors were related to (a) the health care system they work within, (b) the communities where they live, (c) their current practice context, (d) how their participation choices were visible to others, (e) the risks of participation to themselves and others, (f) time factors, (g) the impact of participation on the patient's family, and (h) patient–HCP relationship, and contextual factors. Practice considerations to support the evolving social contact of care were identified.